1969
DOI: 10.1152/ajplegacy.1969.217.6.1619
|View full text |Cite
|
Sign up to set email alerts
|

Fetal brain-maternal aorta temperature differences in sheep

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1971
1971
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Considering that pregnancy is a hypermetabolic and hyperdynamic state, perhaps a hypothermic response to infectious stimuli aimed at energy conservation, which defends the host's vital systems is of greater survival value than the antimicrobial and immunostimulating effects of a febrile response. Fetal Tc is normally "clamped" 0.4°C to 0.8°C higher than maternal Tc, (1), and in some species, such as the sheep, where the febrile response to bacterial pyrogen occurs until very late in gestation, fetal Tc increases in parallel (1,23) or exceeds (30) the rise in maternal Tc with a resulting increase in oxygen demand secondary to the temperature coefficient of metabolism (i.e., Q 10 ). If this occurred at a time when fetal oxygen availability was limited, such as asphyxia during birth, it could potentially exacerbate neuronal injury (11,31) and increase perinatal morbidity and mortality.…”
Section: Perspectives and Significancementioning
confidence: 99%
“…Considering that pregnancy is a hypermetabolic and hyperdynamic state, perhaps a hypothermic response to infectious stimuli aimed at energy conservation, which defends the host's vital systems is of greater survival value than the antimicrobial and immunostimulating effects of a febrile response. Fetal Tc is normally "clamped" 0.4°C to 0.8°C higher than maternal Tc, (1), and in some species, such as the sheep, where the febrile response to bacterial pyrogen occurs until very late in gestation, fetal Tc increases in parallel (1,23) or exceeds (30) the rise in maternal Tc with a resulting increase in oxygen demand secondary to the temperature coefficient of metabolism (i.e., Q 10 ). If this occurred at a time when fetal oxygen availability was limited, such as asphyxia during birth, it could potentially exacerbate neuronal injury (11,31) and increase perinatal morbidity and mortality.…”
Section: Perspectives and Significancementioning
confidence: 99%
“…IMAI-MATSUMARA AND OTHERS In previous studies, fetal body temperature has been shown to parallel maternal temperature (Abrams, Caton, Curet, Crenshaw, Mann & Barron, 1969;Gunn & Gluckman, 1983). Therefore, when the body temperatures of pre-0-day pregnant rats in the present study dropped by 4 0C in the cold, fetal temperature probably decreased correspondingly.…”
mentioning
confidence: 96%
“…Since this kind of change is well correlated to a reduction in thyroid hormone secretion rate in the adult, the results suggest that the thyroid gland participates in active neuroen docrine regulation of heat production in the fetus. Previous studies have shown that the fetus is warmer than the mother by 0.5-1.0 °C and that the fetal-maternal tempera ture gradient is maintained during maternal hyperthermia induced by external heating [17][18][19][20]. It is therefore likely that fetal tem peratures in the vicinity of 41 °C were present in the heat-stressed ewes.…”
Section: Discussionmentioning
confidence: 99%
“…The difference in rectal tempera ture between the two groups was significant (unpaired t = 7.69, df = 18; p < 0.01). Since the normal fetomaternal temperature differ ence is maintained over a range of maternal temperatures [17][18][19], fetal temperature would probably be 0.6-1.0 °C above both the normal and hyperthermic maternal val ues and would therefore have reached 41 °C in the heated group [19], Fetal temperatures were not measured at autopsy, since the measurements would not accurately reflect fetal temperatures in utero.…”
Section: Emperaturesmentioning
confidence: 99%